Canada : surviving the wild north [videorecording (DVD)] - Morris, Patrick, 1966-; Morris, Patrick, 1966-; White, Verity; White, Verity; Bateman, John Christian (PBS, 2022)
Our film begins in high summer in Hudson Bay in Canada's Far North, where polar bears have learned to ambush beluga whales, which visit warm river estuaries to breed. It's a crucial time window, at a difficult time of year. In the vast swathes of tundra, a pair of Arctic foxes gather and bury snow geese eggs, and hunt the chicks, for their fast-growing pups. And in Canada's Bay of Fundy, which has the most extreme tides on Earth, vast flocks of semi-palmated sandpipers arrive on their journey from the Arctic to South America, to feed on mating mud shrimps. But they must beware of hunting peregrine falcons.